UPAYA PENINGKATAN PENGETAHUAN MELALUI KELAS IBU TENTANG GIZI IBU HAMIL DI PUSKESMAS LUBUK ALUNG - Endang Sari; Welly Handayani; Novia Rita Aninora; Mekar Zenny Radhia; Hanifa Zaini; Dewi Asmawati; Elwitri Silvia (COVIT (Community Service of Health), 2022)
Adequate nutritional intake is needed by pregnant women, these nutritional needs are needed for pregnant women to be able to provide good nutrition to the fetus for fetal growth and development in the womb. Pregnant mothers class activities are a means to study groups about health for pregnant women in the form of face to face. The form of community service activities carried out is the implementation of counseling about balanced nutrition for pregnant women and the provision of supplementary food for pregnant women in the pregnant mothers class at Nanggalo Public Health Center in September 2022. The purpose of this activity is so that all pregnant women who are in the class of pregnant women Lubuk Alung Community Health Center knows about balanced nutrition that must be consumed during pregnancy. The results of this community service are all pregnant women who are in the class of pregnant women Lubuk Alung Health Center knows about the benefits and balanced nutrition that must be consumed during pregnancy. Pregnant women with good nutritional knowledge are expected to be able to choose foods that are of good nutritional value and balanced for themselves, the fetus and family Keywords: Knowledge, Nutrition for Pregnant Women